Statin Treatment and Clinical Outcomes of Heart Failure Among Africans: An Inverse Probability Treatment Weighted Analysis - Kwadwo Osei Bonsu; Isaac Kofi Owusu; Kwame Ohene Buabeng; Daniel D. Reidpath; Amudha Kadirvelu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundRandomized control trials of statins have not demonstrated significant benefits in outcomes of heart failure (HF). However, randomized control trials may not always be generalizable. The aim was to determine whether statin and statin type–lipophilic or –hydrophilic improve long‐term outcomes in Africans with HF. Methods and ResultsThis was a retrospective longitudinal study of HF patients aged ≥18 years hospitalized at a tertiary healthcare center between January 1, 2009 and December 31, 2013 in Ghana. Patients were eligible if they were discharged from first admission for HF (index admission) and followed up to time of all‐cause, cardiovascular, and HF mortality or end of study. Multivariable time‐dependent Cox model and inverse‐probability‐of‐treatment weighting of marginal structural model were used to estimate associations between statin treatment and outcomes. Adjusted hazard ratios were also estimated for lipophilic and hydrophilic statin compared with no statin use. The study included 1488 patients (mean age 60.3±14.2 years) with 9306 person‐years of observation. Using the time‐dependent Cox model, the 5‐year adjusted hazard ratios with 95% CI for statin treatment on all‐cause, cardiovascular, and HF mortality were 0.68 (0.55–0.83), 0.67 (0.54–0.82), and 0.63 (0.51–0.79), respectively. Use of inverse‐probability‐of‐treatment weighting resulted in estimates of 0.79 (0.65–0.96), 0.77 (0.63–0.96), and 0.77 (0.61–0.95) for statin treatment on all‐cause, cardiovascular, and HF mortality, respectively, compared with no statin use. ConclusionsAmong Africans with HF, statin treatment was associated with significant reduction in mortality.